Z problematyki czynów przepołowionych - Liżyńska, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The proces of “transferring” some of the petty crimes into acategory of misdemeanors was started by the Act of June 17, 1966 on transferring some petty crimes as misdemeanors to the criminal-administrative jurisdiction. Despite numerous critical opinions about hybrid offences, they still exist. The author in this paper shows the evolution of the transfer of certain crimes into a category of misdemeanors. She points out the need to eliminate hybrid offences, and at the same time to return to the original character of petty crimes law. She emphasizes the need for elimination of differences in criminal liability for juridically identical acts, which are petty crimes and misdemeanors.
Keywords: drobne przestępstwa; czyny przepołowione; przestępstwa mieszane; wykroczenia